Metallic Object within the Knee Joint: A Consequence of Abnormal Sitting Position in a Tricycle - Salawu, Oni Nasiru; Kolade, A O (Nigerian Journal of Orthopaedics and Trauma, 2019)
The use of tricycle as a means of transport is becoming more popular across the rural and urban areas in Nigeria. This article reports a case of a 34‑year‑old woman who sat with her right knee protruding outside the body of the tricycle; while it was on motion, she hit her knee against part of metallic scraps being pushed in opposite direction. X‑ray confirmed the presence of the object around her knee joint, she had surgery to remove the object and she recovered fully from the injury after the surgery. Proper sitting position while inside tricycle is very essential to prevent some avoidable injuries.